2000
DOI: 10.1042/bst028a064
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor-interacting nuclear proteins

Abstract: In the search for androgen receptor (AR) coregulators, we have recently identified four novel proteins that recognize AR zinc finger region both in vivo and in vitro and activate AR-dependent transcription. One of the proteins is a small nuclear RING finger protein (SNURF) that possesses two interaction interfaces; one for AR and another one for other activators of transcription such as Spl. The second protein is a nuclear Ser/Thr protein kinase (ANPK). This nuclear protein kinase augments specifically AR-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…Upon androgen binding, AR regulates the transcription of specific target genes by binding to specific DNA response elements, androgen response elements (AREs), in their promoters. After binding DNA, AR interacts with components of the basal transcription machinery and a variety of general and gene-specific cofactors, resulting in positive or negative effects on gene transcription (Janne et al 2000, Gelmann 2002, Heinlein & Chang 2002. A panel of proteins that can interact with the AR have been identified (ww2.mcgill.ca/androgendb/ARinteract.pdf).…”
Section: Introductionmentioning
confidence: 99%
“…Upon androgen binding, AR regulates the transcription of specific target genes by binding to specific DNA response elements, androgen response elements (AREs), in their promoters. After binding DNA, AR interacts with components of the basal transcription machinery and a variety of general and gene-specific cofactors, resulting in positive or negative effects on gene transcription (Janne et al 2000, Gelmann 2002, Heinlein & Chang 2002. A panel of proteins that can interact with the AR have been identified (ww2.mcgill.ca/androgendb/ARinteract.pdf).…”
Section: Introductionmentioning
confidence: 99%
“…Namely PIAS [protein inhibitor of activated STAT (signal transducer and activator of transcription)] proteins promote SUMOylation of transcription factors in a manner that resembles the action of RINGtype ubiquitin E3 ligases [40]. Since PIASxα/ARIP3 (androgen receptor-interacting protein) [41] [42,43] is involved in nuclear receptor regulation we studied the effect of a forced expression on ERRγ regulation. Our data do not support a specific effect (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis of the RF-1 in the context of a GAL4 fusion protein revealed that all mutants proposed to inhibit sumoylation led to a higher activity of the AF-1. Similarly, a Lys 40 to arginine mutant, as well as the mutation of the hydrophobic residue Ile 39 and of the acidic residue Glu 42 to alanine led to higher activity of full-length ERRγ2. Both, superactivation by replacing the potential phosphorylation acceptor Ser 45 with alanine and a phosphorylation-dependent mobility shift of protein DNA complexes during gel electrophoresis speak in favor of a functional PDSM.…”
mentioning
confidence: 97%
“…[5][6][7] Interestingly, a number of AR co-activators display diverse patterns of expression in prostate cancer. For example, the AR cofactors ARA24, PIAS1, 8 cyclinD1, 9 SRC1, 10 and FHL2 11 appear overexpressed, whereas ARA70 8 and ART-27 12 are reduced in human prostate cancers compared to adjacent benign tissue.…”
mentioning
confidence: 99%
“…3,4 An increasing number of AR-interacting proteins have been identified, and several have been shown to function as AR co-activators in cellbased reporter assay. [5][6][7] Interestingly, a number of AR co-activators display diverse patterns of expression in prostate cancer. For example, the AR cofactors ARA24, PIAS1, 8 cyclinD1, 9 SRC1, 10 and FHL2 11 appear overexpressed, whereas ARA70 8 and ART-27 12 are reduced in human prostate cancers compared to adjacent benign tissue.…”
mentioning
confidence: 99%